RELASI AGAMA DAN BUDAYA DALAM SEJARAH PEMERINTAHAN KESULTANAN BIMA - Irwan Supriadin J (STIT Sunan Giri Bima, 2023)
This study aims to examine literature sources related to the combination of religion, culture and government of the Bima Sultanate. The research method uses literature review from the main source of the Book of Bo and other supporting literature sources. The data, theory and findings are then analyzed to draw a conclusion about the relationship between religion and culture in government. This research then found that the Bima Sultanate was one of the sultanates in the archipelago that integrated religion and custom in the political structure of its government. The Sultan as the supreme ruler is accompanied by the Hadat Assembly headed by Ruma Speech and the Syara Council headed by Qadhi, each of whom provides input and considerations in all aspects of governance although in certain cases the Sultan has previllage rights which can ignore all considerations from the Hadat Council and Sharia Council'. The Hadat Council and Syara Council have equality in considering the Sultan's candidates up to the inauguration procession of the elected Sultan. Islamic law is one of the legal foundations of government other than customary law which has been running since the kingdom. The Syara' Council plays an important role in Islamic da'wah and broadcasting activities, besides that the Syara' Council is also responsible for the continuity of education throughout the empire.